Modeling tangential contact of lap joints considering surface topography based on Iwan model. (September 2019) - Chen, Jian; Zhang, Jinhua; Hong, Jun; Zhu, Linbo
Abstract: A contact model to capture the tangential responses of lap joints is proposed. Based on the micro-contact theory and the Coulomb friction law, the tangential contact of the contacting asperities undergone certain normal load is simplified to Jenkins element in the parallel-series Iwan model, then a continuous function possessing an explicit physical significance is developed to describe the yield force distribution of the contacting asperities on the joint interface. In order to validate the proposed model, the predicted results are compared with the published experimental results. A definition and a criterion of slip ratio are introduced to quantifiably evaluate the contact states of lap joints. The influencing factors of the distribution function and the slip ratio were analyzed. Highlights: A tangential contact model is proposed considering the surface topography of lap joints. A continuous distribution function is developed to describe the yield force distribution of the contacting asperities on the joint interface. A definition and a criterion of slip ratio are introduced to quantifiably evaluate the contact states of lap joints.